2012
DOI: 10.1099/vir.0.038661-0
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Epstein–Barr virus infection in epithelial cells but not in B-lymphocytes is dependent on Blimp1

Abstract: Epstein-Barr virus (EBV) replicates in superficial differentiated cells of oral hairy leukoplakia (OHL). Differentiation of squamous epithelial cells depends on B-lymphocyte-induced maturation protein 1 (Blimp1).Here we show that expression of the EBV immediate-early protein BZLF1 is restricted to Blimp1-positive epithelial cells in OHL. Luciferase assays revealed Blimp1-dependent induction of the BZLF1 promoter Zp in epithelial cell lines. Expression of ZEB1, a negative regulator of Zp, and of Xbp-1, which me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…1). Consistent with our findings, Buettner et al (59) observed that all Z ϩ cells within an OHL lesion are also BLIMP1 ϩ , while only onethird to two-thirds of Z ϩ B cells from tonsils of IM patients contain detectable BLIMP1. Thus, we conclude that BLIMP1 expression leads to induction of EBV lytic gene expression in many (possibly all) EBV ϩ epithelial cell types but not all EBV ϩ B-cell types.…”
Section: Blimp1-induced Ebv Reactivationsupporting
confidence: 93%
See 2 more Smart Citations
“…1). Consistent with our findings, Buettner et al (59) observed that all Z ϩ cells within an OHL lesion are also BLIMP1 ϩ , while only onethird to two-thirds of Z ϩ B cells from tonsils of IM patients contain detectable BLIMP1. Thus, we conclude that BLIMP1 expression leads to induction of EBV lytic gene expression in many (possibly all) EBV ϩ epithelial cell types but not all EBV ϩ B-cell types.…”
Section: Blimp1-induced Ebv Reactivationsupporting
confidence: 93%
“…9). Combining all of our findings together with those of Buettner et al (59), we conclude that this activation of BLIMP1 expression may well be necessary as well as sufficient in epithelial cells, but not in B cells, for induction of EBV reactivation.…”
Section: Blimp1-induced Ebv Reactivationsupporting
confidence: 84%
See 1 more Smart Citation
“…Work done when OHL lesions were more readily available indicated that replication in these lesions was restricted to the upper, more differentiated layers (15,16). More recently, virus expression has been shown to be limited to cells expressing B-lymphocyteinduced maturation protein 1 (Blimp1), which is up-regulated during epithelial differentiation, and the promoter of one of the immediate early genes of EBV is responsive to Blimp1 (17). The work of Temple et al now provides further support for a model in which replication is linked to differentiation.…”
Section: Demonstration Of Direct Entry Of Ebv Into Lytic Replication mentioning
confidence: 99%
“…EBV establishes long-term latency in B cells, undergoing reactivation when they differentiate into plasma cells (2). Some Bcell-specific factors (e.g., Oct-2 and Pax-5) promote EBV latency (14,15), while some plasma-cell-specific factors (e.g., XBP-1s and BLIMP-1) promote EBV lytic replication (6,7,70,71). To further understand how Ikaros contributes to EBV latency, we examined the effect of changing its level on the expression of some cellular factors known to play key roles in regulating EBV's latent-lytic switch or B-cell differentiation into plasma cells.…”
Section: Ikaros Contributes To Maintenance Of Ebv Latency In B Cellsmentioning
confidence: 99%